2017
DOI: 10.3174/ajnr.a5313
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Biomarkers for Adult Medulloblastomas: Genetic Entities May Be Identified by Their MR Imaging Radiophenotype

Abstract: MR imaging biomarkers can help distinguish histologic and genetic medulloblastoma entities in adults and appear to be different from those identified in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
2
16
1
Order By: Relevance
“…In an imaging study exclusively involving children with WNT-subgroup medulloblastoma (n = 16), Patay et al [26] reported the involvement of specific sites such as foramen of Luschka (75%), IVth ventricle (69%), cisterna magna (31%) and CPA cistern (19%). The anatomic location of WNT-subgroup tumors was found to be similar even in adult WNT-subgroup tumors (n = 4), with 75% being or reaching the midline in the IVth ventricle [27] . In an exclusive cohort of adult medulloblastomas, Zhao et al [28] reported midline vermian location in 5 of 17 (29%) WNT-pathway tumors and lateral extension into cerebellar hemisphere or peduncle in the remaining 12 (71%) patients.…”
Section: Anatomic Locationmentioning
confidence: 85%
See 4 more Smart Citations
“…In an imaging study exclusively involving children with WNT-subgroup medulloblastoma (n = 16), Patay et al [26] reported the involvement of specific sites such as foramen of Luschka (75%), IVth ventricle (69%), cisterna magna (31%) and CPA cistern (19%). The anatomic location of WNT-subgroup tumors was found to be similar even in adult WNT-subgroup tumors (n = 4), with 75% being or reaching the midline in the IVth ventricle [27] . In an exclusive cohort of adult medulloblastomas, Zhao et al [28] reported midline vermian location in 5 of 17 (29%) WNT-pathway tumors and lateral extension into cerebellar hemisphere or peduncle in the remaining 12 (71%) patients.…”
Section: Anatomic Locationmentioning
confidence: 85%
“…In the series by Patay et al [26] , hemorrhage was appreciated on pre-operative imaging in 31% of children with WNT-subgroup medulloblastoma (n = 16). On the contrary, Keil et al [27] , reported absence of hemorrhage on imaging in all 4 cases of adult WNT-pathway medulloblastoma. However, in another study involving adult patients [28] , hemorrhage or mineralization was reported in 11 of 17 (67%) WNT-pathway medulloblastoma.…”
Section: Intra-tumoral Hemorrhagementioning
confidence: 93%
See 3 more Smart Citations